Analisis Potensi Pengembangan Pembiayaan Natural Uncertainty Contract (NUC) pada Sektor Produktif di Bank Pembiayaan Rakyat Syariah (BPRS) - Trimulato Trimulato (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2018)
The growth of Islamic banks in Indonesia is getting better. People who interested in using Islamic bank products continues to arise. The market share of Islamic banks currently has reached 5.8 percent of the total market share of banks nationally. Natural Uncertainty Contract (NUC) with profit sharing pattern using mudharabah and musyarakah contracts is one of the productive financing products of Islamic bank which is not owned by conventional bank. However, in Islamic rural banks (BPRS), nonproductive financing is more dominant. This qualitative study would like to explain the financing of NUC in the BPRS. The result shows that the growth of NUC financing is still very small, musharaka only grew 0.23 percent and mudharabah decreased by 20.23 percent during 2016-2017. Overall, financing distribution in BPRS is still dominated by consumptive financing, amounting to 46.07 percent. While for productive financing has not become a priority in the BPRS. Keywords: BPRS, Natural Uncertainty Contract.